Les images paysagères autour du thé et de la Chine dans la publicité : quels simulacres de paysage ? - Yun Zhang (Projets de Paysage)
Based on documentary work and a survey of two areas around the cities of Fujian Province (Wuyi Mountains and Fuzhou), the article considers the genesis of the tea-growing landscape and its image. This tea-growing landscape, born of the domestication of wild plants and which is at the origin of many tangible and intangible representations, is not only an oriental construction, it is also the result of many contributions from the West. This article describes the use of the image of tea and its landscape in advertising, focusing on several periods (the late 19th century, early 20th century and the period following the economic reforms in China in the 1980s). Also studied are other images based on the tea-growing landscape created for the purpose of advertising. The objective is to understand how and in what form the tea-growing landscape, which has been built over time by these representations, is consumed today.